2009
DOI: 10.1017/s0022381609990211
|View full text |Cite
|
Sign up to set email alerts
|

“New-Style” Judicial Campaigns and the Legitimacy of State High Courts

Abstract: Judicial elections in the American states became considerably more complicated with the U.S. Supreme Court's decision in Republican Party of Minnesota v White. That ruling extended free speech rights to candidates for judicial office, allowing them the freedom to announce their views on a variety of political and legal issues. Coupled with growing campaign contributions by interest groups and the increasing prevalence of attack ads, state judicial elections now often appear to be little different from ordinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…The findings largely coincide with the literature concerning the effect of campaigning on perceived legitimacy. That literature concentrates on examining the effect of specific types of campaign activity like politicized television advertisements (Gibson 2008a;Gibson et al 2011) or accepting campaign contributions (Gibson 2008b(Gibson , 2009). The current study did not examine specific types of campaign activity but instead attempted to assess the overall amount of campaign activity through indicators of election activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings largely coincide with the literature concerning the effect of campaigning on perceived legitimacy. That literature concentrates on examining the effect of specific types of campaign activity like politicized television advertisements (Gibson 2008a;Gibson et al 2011) or accepting campaign contributions (Gibson 2008b(Gibson , 2009). The current study did not examine specific types of campaign activity but instead attempted to assess the overall amount of campaign activity through indicators of election activity.…”
Section: Resultsmentioning
confidence: 99%
“…These studies, taken together, suggest that campaign ads do decrease legitimacy, but those portraying judges as ordinary politicians have the greatest negative effect. Gibson (2008bGibson ( , 2009) examines the effect of campaign contributions on perceived legitimacy and finds that accepting contributions from judges and litigants decreases perceived legitimacy. These types of studies, specifically examining the effect of campaign activity, cannot assess the overall effect of elections on legitimacy because they neglect the positive boost provided by electoral accountability.…”
Section: Existing Researchmentioning
confidence: 99%
“…Notwithstanding, Gibson (2012, 111) provides empirical support that "politicized campaigning is unlikely to affect legitimacy" (see also Gibson 2009;Hall and Bonneau 2013). While judicial legitimacy is tangentially related to our study, we are concerned specifically with the concepts of accountability and independence based on judicial careers.…”
Section: Judicial Selection Careers and Riskmentioning
confidence: 99%
“…For many citizens, contributions to candidates for judicial office imply a conflict of interest, even a quid pro quo relationship between the donor and the judge, which undermines perceived impartiality and legitimacy. These conclusions from Kentucky have been subsequently replicated in a national survey (see Gibson 2009a). It is important to note, however, that the judiciary is not distinctive on this score: Gibson finds that campaign contributions to candidates for the state legislature also imply a conflict of interest and therefore can detract from the legitimacy of legislatures as well.…”
mentioning
confidence: 90%
“…Campaign contributions are not. Although the literature is certainly fragmentary, a handful of recent studies has demonstrated the quite negative consequences of campaign contributions in general for the institutional legitimacy of courts (e.g., Gibson 2008aGibson , 2008bGibson , 2009a. The American people seem not to be bothered by statements of policy positions and even policy promises by judicial candidates, or by the use of advertisements attacking opponents.…”
mentioning
confidence: 99%